Efektivitas Model PjBL (Project-Based Learning) dalam Meningkatkan Hasil Belajar Kognitif Peserta Didik dengan Gaya Belajar Berbeda - Akbar, Fauzan; Bahri, Arsad (Biology Teaching and Learning, 2018)
This research is a quasi-experimental study that aims to determine the effectiveness of the implementation of Project-based Learning (PjBL) in improving students' cognitive learning outcomes with different learning styles namely visual, audio and kinesthetic learning styles. The population of this study was all groups at X grade in Public High School 1 Bulukumba. Sample of the study was choosed by random sampling. Each learning model was represented by two groups as PjBL and Direct Instruction. The research sample used was group XI IPA 1, XI IPA 2, XI IPA 3, and XI IPA 4. The design of this study was pretest-posttest nonequivalent control group design factorial pattern 2 x 3. The research instrument consisted of essay tests to measure cognitive learning outcomes and students learning style questionnaire. The research data were analyzed using descriptive and inferential statistics with two-way analysis of covariate (ANCOVA). The results showed that PjBL and learning styles had an effect on students 'cognitive learning outcomes, while the interaction between learning models and learning styles did not affect students' cognitive learning outcomes. This shows that PjBL is effective in improving students' cognitive learning outcomes.Keywords: Project-based Learning, learning styles, cognitive learning outcomes, biology learning